The China Tax Guide - Devonshire-Ellis, Chris; Scott, Andy.; Woollard, Sam.; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This guide is a practical overview for the international businessman to understand the rules, regulations and management issues regarding taxes in China. It is written very much from practical experience. We will help you to understand the implications of what can initially appear be a complicated and contradictory subject. This book tells you the basics of what you need to know, and point you at the structures you should use to enable your China business to be both in compliance and as tax efficient as possible.
Tax Planning -- China's Tax Law and Administration -- Corporate Income Tax, Value-added Tax, Withholding Tax and Business Tax -- Representative Office Tax Treatments -- Export Tax Rebates -- Consumption Tax Rates -- Expatriate Individual Income Tax and Permitted Benefit Allowances -- Statutory Audit Obligations for Foreign Enterprises -- General Accounting Treatments on Significant Audit Areas -- Annual Audit Issues Commonly Queried Upon Inspection -- Related Party Transaction Documentation Requirements -- China?s Double Tax Treaties -- Regulations Concerning China-Hong Kong Cross Border Treatments.
Electronic reproduction.
Keywords: Taxation -- Law and legislation -- China; Business enterprises, Foreign -- Taxation -- Law and legislation -- China; Aliens -- Taxation -- Law and legislation -- China